Associations of Internalizing and Externalizing Problems with Facial Expression Recognition in Preschoolers: The Generation R Study. Issue 3 (27th December 2013) - Székely, Eszter; Tiemeier, Henning; Jaddoe, Vincent W. V.; Hofman, Albert; Verhulst, Frank C.; Herba, Catherine M.
Abstract Altered patterns of facial expression recognition (FER) have been linked to internalizing and externalizing problems in school children and adolescents. In a large sample of preschoolers (N = 727), we explored concurrent and prospective associations between internalizing/externalizing problems and FER. Internalizing/externalizing problems were rated by parents at 18 and 36 months using the Child Behavior Checklist. FER was assessed at 36 months using age‐appropriate computer tasks of emotion matching and emotion labeling. Internalizing problems were associated with emotion‐specific differences at both ages: at 18 months they predicted more accurate labeling of sadness; at 36 months they were associated with less accurate labeling of happiness and anger. Externalizing problems at both ages were associated with general FER deficits, particularly for matching emotions. Findings suggest that in preschoolers, internalizing problems contribute to emotion‐specific differences in FER, while externalizing problems are associated with more general FER deficits. Knowledge of the specific FER patterns associated with internalizing/externalizing problems can be proven useful in the refinement of emotion‐centered preventive interventions.